2019
DOI: 10.1108/ijlss-03-2018-0027
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the leanness of a supply chain using multi-grade fuzzy logic: a health-care case study

Abstract: Purpose Numerous and diverse organizations have implemented lean principles and practices, which concentrate on improving the efficiency of business processes by reducing cost, waste, consumptions and effort. However, previous assessments have not focused on the leanness of the supply chain in a health-care setting. This paper aims to introduce a method for assessing the successful implementation of lean principles and tools in a supply chain. Furthermore, this paper validates the method in a health-care organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 86 publications
(128 reference statements)
0
52
0
Order By: Relevance
“…The multi-grade fuzzy approach is extensively applied in manufacturing and service sectors for assessment of leanness, agility, marketing flexibility, safety practice level and service level [1,12,21,24,[27][28][29][30][31][32]. The current study utilises multi-grade fuzzy to assess the efficiency of the work-from-home model among software professionals.…”
Section: Multi-grade Fuzzymentioning
confidence: 99%
“…The multi-grade fuzzy approach is extensively applied in manufacturing and service sectors for assessment of leanness, agility, marketing flexibility, safety practice level and service level [1,12,21,24,[27][28][29][30][31][32]. The current study utilises multi-grade fuzzy to assess the efficiency of the work-from-home model among software professionals.…”
Section: Multi-grade Fuzzymentioning
confidence: 99%
“…In recent years multi-grade fuzzy approach has been widely used in various fields in the literature particularly in operations management field (Almutairi et al, 2019;Mishra and Mishra, 2018). For example, Kalyan et al, (2019) developed an index to measure industrial symbiosis of a tire-manufacturing organisation using multi-grade fuzzy approach.…”
Section: Multi-grade Fuzzy Logicmentioning
confidence: 99%
“…Numerous and diverse organizations have implemented lean principles and practices, which concentrate on improving the efficiency of business processes by reducing cost, waste, consumptions and effort. Almutairi et al [58] suggested a model as to enable decision makers in hospital supply chain to take suitable actions for improving lean implementation level. Healthcare institutions, as any other investigation, need to be able to assess their current level of leanness as at lease a starting point for implementing lean [11,55].…”
Section: Absence Of the Required Level Of Leanness (B8)mentioning
confidence: 99%